7x-3=4-2x

Simple and best practice solution for 7x-3=4-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3=4-2x equation:


Simplifying
7x + -3 = 4 + -2x

Reorder the terms:
-3 + 7x = 4 + -2x

Solving
-3 + 7x = 4 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3 + 7x + 2x = 4 + -2x + 2x

Combine like terms: 7x + 2x = 9x
-3 + 9x = 4 + -2x + 2x

Combine like terms: -2x + 2x = 0
-3 + 9x = 4 + 0
-3 + 9x = 4

Add '3' to each side of the equation.
-3 + 3 + 9x = 4 + 3

Combine like terms: -3 + 3 = 0
0 + 9x = 4 + 3
9x = 4 + 3

Combine like terms: 4 + 3 = 7
9x = 7

Divide each side by '9'.
x = 0.7777777778

Simplifying
x = 0.7777777778

See similar equations:

| -6+4(3x-13)=82 | | 2*y-3*y=5 | | 8x+1=1.528 | | -2m-8m=10 | | 24x=24x-27 | | (x+7)2+(y-1)2=32 | | x=52.5(2/5) | | u^2=3u | | k(x)=2x^2+33x-54 | | x=40(2/5) | | 11=11-10b+2b | | s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 |

Equations solver categories